Polymorphism of the second type angiotensin II receptor’s gene in women with essential hypertension and the corresponding features of structural and functional parameters of myocardium - O. O. Sakovych; V. M. Zhebel; T. V. Polishchuk; S. V. Franchuk; L. M. Sursaieva (Patologìâ)
Abstract